Association between serum ferritin and mortality: findings from the USA, Japan and European Dialysis Outcomes and Practice Patterns Study. Issue 12 (11th July 2018) - Karaboyas, Angelo; Morgenstern, Hal; Pisoni, Ronald L; Zee, Jarcy; Vanholder, Raymond; Jacobson, Stefan H; Inaba, Masaaki; Loram, Lisa C; Port, Friedrich K; Robinson, Bruce M
ABSTRACT: Background: The Kidney Disease: Improving Global Outcomes guidelines have cautioned against administering intravenous (IV) iron to hemodialysis patients with high serum ferritin levels due to safety concerns, but prior research has shown that the association between high ferritin and mortality could be attributed to confounding by malnutrition and inflammation. Our goal was to better understand the ferritin–mortality association and relative influence of IV iron and inflammation in the USA, where ferritin levels have recently increased dramatically, and in Europe and Japan, where ferritin levels are lower and anemia management practices differ. Methods: Data from 18 261 patients in Phases 4 and 5 (2009–15) of the international Dialysis Outcomes and Practice Patterns Study, a prospective cohort study, were analyzed. Using Cox regression, we modeled the association between baseline ferritin and 1-year mortality with restricted cubic splines and assessed the impact of potential confounders. Results: Median ferritin levels were 718 ng/mL in the USA, 405 in Europe and 83 in Japan. High ferritin levels were associated with elevated mortality (relative to region-specific medians) in all three regions. The strength of this association was attenuated more by adjustment for malnutrition and inflammation than by IV iron and erythropoiesis-stimulating agent dose in each region. Conclusion: The utility of high ferritin as a biomarker for clinical risk due to excess iron stores may be limited, although caution regarding IV iron dosing to higher upper ferritin targets remains warranted. Research to resolve biomarker criteria for iron dosing, and whether optimal anemia management strategies differ internationally, is still needed.